Understanding the implementation strategy of a secondary care tobacco addiction treatment pathway (the CURE project) in England: a strategic behavioural analysis. Issue 6 (14th June 2022) - Rodrigues, Angela M; Wearn, Angela; Haste, Anna; Mallion, Verity; Evison, Matthew; Howle, Freya; Haighton, Catherine
Abstract : Objectives: The Conversation, Understand, Replace, Experts and evidence-based treatment (CURE) project implemented an evidence-based intervention that offers a combination of pharmacotherapy and behavioural support to tobacco-dependent inpatients. Understanding key characteristics of CURE's implementation strategy, and identifying areas for improvement, is important to support the roll-out of nationwide tobacco dependence services. This study aimed to (1) specify key characteristics of CURE's exiting implementation strategy and (2) develop theoretical-informed and stakeholder-informed recommendations to optimise wider roll-out. Design and methods: Data were collected via document review and secondary analysis of interviews with 10 healthcare professionals of a UK hospital. Intervention content was specified through behaviour change techniques (BCTs) and intervention functions within the Behaviour Change Wheel. A logic model was developed to specify CURE's implementation strategy and its mechanisms of impact. We explored the extent to which BCTs and intervention functions addressed the key theoretical domains influencing implementation using prespecified matrices. The development of recommendations was conducted over a two-round Delphi exercise. Results: We identified six key theoretical domains of influences: 'environmental context and resources', 'goals', 'social professional role and identity', 'social influences', 'reinforcement' and 'skills'. The behavioural analysis identified 26 BCTs, 4 intervention functions and 4 policy categories present within the implementation strategy. The implementation strategy included half the relevant intervention functions and BCTs to target theoretical domains influencing CURE implementation, with many BCTs focusing on shaping knowledge. Recommendations to optimise content were developed following stakeholder engagement. Conclusions: CURE offers a strong foundation from which a tobacco dependence treatment model can be developed in England. The exiting strategy could be strengthened via the inclusion of more theoretically congruent BCTs, particularly relating to 'environmental context and resources'. The recommendations provide routes to optimisation that are both theoretically grounded and stakeholder informed. Future research should assess the feasibility/acceptability of these recommendations in the wider secondary-care context.